2019
DOI: 10.1007/s11205-019-02212-x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Trust and Subjective Well-Being Across Europe: New Insights from Repeated Cross-Sectional Analyses Based on the European Social Survey 2002–2016

Abstract: This paper offers elaborate analyses regarding the effects of social-as well as institutional trust as parts of social capital on subjective well-being (SWB) by using data from the European Social Survey, including 36 countries and eight time-points between 2002 and 2016. We analyze (1) The development of trust and SWB on the aggregate level; (2) The effect of trust on SWB on the individual cross-sectional level; and (3) The longitudinal and crosssectional effect of trust on SWB on the aggregate level while co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 61 publications
1
25
1
Order By: Relevance
“…A substantially higher significance of political trust to wellbeing in transition countries as compared to economically more developed countries in Europe, as well as a reduced association in the Nordic countries have been reported earlier (29,30). One study reported that the relationship between personal life satisfaction and perceived quality of society was weaker in wealthier countries while the opposite was true in poorer countries (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantially higher significance of political trust to wellbeing in transition countries as compared to economically more developed countries in Europe, as well as a reduced association in the Nordic countries have been reported earlier (29,30). One study reported that the relationship between personal life satisfaction and perceived quality of society was weaker in wealthier countries while the opposite was true in poorer countries (31).…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that the relationship between personal life satisfaction and perceived quality of society was weaker in wealthier countries while the opposite was true in poorer countries ( 31 ). This could possibly be another indication of a relationship between political trust and satisfaction with one's personal life, which may indicate that the marginal effect of income is less in the high trust countries, where income is higher ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Calvo et al 2012;Helliwell and Putnam 2004;Portela et al 2013), but also on the aggregate level between countries (e.g. Glatz and Eder 2019;Mikucka et al 2017). Previous studies obtained the same pattern for institutional trust, showing that institutional trust has a positive effect on subjective well-being (e.g.…”
Section: Social Resources and Subjective Well-being: Empirical Evidencementioning
confidence: 59%
“…These are in general consistent with the findings elsewhere (Sønderskov & Dinesen, 2016). For example, multiple studies showed a robust relation between social trust and subjective well‐being (Glatz & Eder, 2020; Graafland & Lous, 2019; Puntscher et al., 2015). Overall, the findings presented above appear to reinforce the argument that tradition, norms, social participation, social networks, and globalization all are at play.…”
Section: Discussionmentioning
confidence: 99%